Review of Tertiary Irrigation Canals in the Durian Lingga Village in the Irrigation Areas of Namu Sira Sira Sei Bingai district of Langkat Guided - Zulficar Zk; Sumono Sumono; Saipul Bahri Daulay (Universitas Sumatera Utara, 2014)
The need of water on the field of durian lingga village was channeled through tertiary canal that made from soil. This can affect the lossing of water. This study was aimed to examine the tertiary irrigation channel in that area. The parameters measured were the physical of soil properties, the discharge channel, the efficiency of the distribution, water loss, flow velocity, slope and size of the channel. The results of the research showed the efficiency of the distribution on line 1 at a distance of 120 m was 63.12% and channel 2 at a distance of 90 m was 66.46%. The efficiency of channeling at a same distance (90 m) with the assumption of losing the water on every meters was the same, was 78.87% on channel 1 and 66.46% on channel 2. The average flow velocity was smaller than the critical speed so that precipitation happened, there for redesign of the channel dimensions was needed. The result of the best design of tertiary channel dimensions for the channel 1 was width of the channel (B) of 0.704 m and depth (D) of 0.352 m with a slope of 0.032%, while for channel 2 the width of the channel (B) was 0.844 m and the depth (D) was 0.422 m with a slope 0.02%. Key Words: tertiary a channel, conveyance efficiency, design of canals.